Enhancing Healthcare Service Quality through Awareness and Participation - Katiyar, Arpana; Sachan, Vivek Singh; Singh, Warshi; Katiyar, Praveen; Martolia, Dinesh Singh; Agarwal, Shivam (Indian Journal of Community Health, 2025)
This study investigates the awareness and participation of medical service seekers in Kanpur concerning local health care service centers and health awareness programs. The research highlights a significant shift in the knowledge and voluntary engagement of medical service seekers, driven by advancements in technology and health care products. The analysis reveals that the variables related to medical service seekers are sufficient to represent the concept of facilities-oriented strategies. Additionally, the study examines the variances in perceptions of medical service seekers regarding these strategies. The findings provide valuable insights into the characteristic features of medical service seekers and their interaction with health care facilities in Kanpur. This research underscores the importance of understanding the evolving needs and behaviors of medical service seekers to enhance the effectiveness of health care services and programs. By identifying key factors that influence awareness and participation, the study offers practical implications for health care providers and policymakers aiming to improve health care delivery and accessibility in Kanpur. The insights gained from this research can inform the development of targeted strategies to increase engagement and satisfaction among medical service seekers. Overall, this study contributes to the broader understanding of health care service utilization and the role of technology and awareness programs in shaping health care behaviors. The findings emphasize the need for continuous assessment and adaptation of health care strategies to meet the dynamic needs of the population, ensuring that health care services are both accessible and effective for all medical service seekers in Kanpur.